ABSENCE OF SUPERCONDUCTIVITY IN THE MIXTURE Y-BA-AG-O - Singh, K; Hunneyball, P; Edwards, P (1991)
In contrast to earlier reports, we find that the mixture Y-Ba-Ag-O does not form a compound 'YBa2Ag3Ox' in a similar fashion to YBa2Cu3O7 but rather is a combination of Ba-Y-O compounds, silver metal and unreacted starting materials. This mixture shows metallic behaviour, but no superconductivity down to 5 K. The observed metallic behaviour of these samples is almost certainly due to the presence of elemental silver. Electron probe micro-analysis (EPMA) studies show that silver does not react with Y, Ba and Ba4Y2O7 in an oxygen atmosphere. The importance of conjoint EPMA/EDAX (energy dispersive X-ray spectroscopy) and X-ray powder diffraction (XRD) studies is emphasised.